Sources and Reactions to Stress in Brazilian Lawyers - Costa, Maria de Fátima Antunes Alves; Ferreira, Maria Cristina (Paidéia (Ribeirão Preto), 2014)
Job stress can negatively affect the health of employees. As such, the investigation of its characteristics in different professional categories is relevant. The aim in this study was to analyze the predictive power of seven stressors (decision latitude, psychological demands at work, physical demands at work, social support from colleagues, ergonomic stressors, relationships with clients, job insecurity) for job dissatisfaction, depression and psychosomatic problems in a sample of 702 Brazilian lawyers. The data were collected using a Brazilian version of the Job Content Questionnaire (JCQ). The results showed that decision latitude and social support were the main negative predictors of stress, while psychological demands and job insecurity were its main positive predictors. These results are discussed in the light of the demand-support-control model, which was used as a framework for the research.